2020
DOI: 10.1038/s41366-020-00713-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of pediatric metabolic syndrome—a critical look on the discrepancies between definitions and its clinical importance

Abstract: Introduction The Metabolic Syndrome (MetS) describes the clustering of cardio-metabolic risk factors—including abdominal obesity, insulin resistance, elevated blood pressure, high levels of triglycerides, and low levels of high-density lipoproteins—that increase the risk for developing cardiovascular diseases and type 2 diabetes mellitus. However, a generally accepted definition of MetS in pediatric patients is still lacking. Objectives The aim was to summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
117
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 74 publications
7
117
1
5
Order By: Relevance
“…The findings of the recent systematic review also revealed that the prevalence of MetS in the pediatric population ranged from 0.3 to 26.4%, with the lower prevalence recorded in the IDF criteria (0.3-9.5%). But, the prevalence was relatively higher in the de Ferranti et al criteria (4-26.4%) [140]. Thus, the current findings are in line with the findings in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the recent systematic review also revealed that the prevalence of MetS in the pediatric population ranged from 0.3 to 26.4%, with the lower prevalence recorded in the IDF criteria (0.3-9.5%). But, the prevalence was relatively higher in the de Ferranti et al criteria (4-26.4%) [140]. Thus, the current findings are in line with the findings in this study.…”
Section: Discussionsupporting
confidence: 92%
“…In our present study, the prevalence of decreased HDL-C levels also increased significantly, from 21.21% to 36.73% ( p = 0.016), in the subgroups aged 20–34 years, while there was no significant change in the other age groups between 2006 and 2018. High prevalence of MetS was also detected among young adults (aged 18–30 years) in a study recently published [ 39 ] on the Ellisras (town in the Limpopo province of South Africa) rural population, and increasing prevalence of MetS even among children and adolescents seems to be a worldwide phenomenon [ 40 , 41 , 42 ]. These observations are interpreted as outcomes of severe nutritional changes and missing preventive interventions targeting healthy diet [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…High prevalence of MetS was also detected among young adults (aged 18–30 years) in a study recently published [ 39 ] on the Ellisras (town in the Limpopo province of South Africa) rural population, and increasing prevalence of MetS even among children and adolescents seems to be a worldwide phenomenon [ 40 , 41 , 42 ]. These observations are interpreted as outcomes of severe nutritional changes and missing preventive interventions targeting healthy diet [ 40 , 41 , 42 ]. Several studies have found that young adults are at increased risk for the development of cardiovascular diseases [ 43 , 44 , 45 ] and for mental disorders [ 46 , 47 ] in the presence of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome (MetS) refers to a clustering of co-incident and interrelated risk factors that place a subject at high risk of developing cardiovascular disease (CVD) and diabetes type 2 (DT2), thus increasing mortality risk [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. These factors include central obesity, dysglycemia/insulin resistance (IR), hypertension, high levels of triglycerides (TG), and low high-density lipoprotein cholesterol (HDL cholesterol) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of pediatric MetS ranges from 0.3 to 26.4%. This variation in prevalence is due to the large number of different pediatric definitions of MetS [ 9 ]. MetS is usually closely linked to overweight and obesity, and it predicts DT2, CVD, and all-cause mortality in adults [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%